2017
DOI: 10.14309/crj.2017.14
|View full text |Cite
|
Sign up to set email alerts
|

Two Complex Cases of Hermansky-Pudlak Syndrome Highlight a Potential Biologic Explanation for an Associated Crohn's Disease Phenotype

Abstract: Hermansky-Pudlak syndrome (HPS) is a rare autosomal recessive disorder characterized by oculocutaneous albinism and a lack of dense granules in platelets. HPS types 1 and 4 are associated with a granulomatous enterocolitis that is phenotypically indistinguishable from Crohn’s disease. We present two cases of HPS-associated Crohn’s disease phenotype in which the patients were refractory to standard medical management. The pathophysiology of HPS is mediated by single-gene defects that alter endosome trafficking,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Granulomatous colitis was described as a complication of HPS for the first time in 1980[8]. Since then, many cases of inflammatory bowel disorders have been described, including those of colitis, enterocolitis or perianal disease[3,4,9-12]. These gastrointestinal complications are associated with HPS 1 and HPS 4 subtypes, occur in 20%-30% of the cases[3,4], and have been the cause of death in 9% of the deceased HPS patients in Puerto Rico[6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Granulomatous colitis was described as a complication of HPS for the first time in 1980[8]. Since then, many cases of inflammatory bowel disorders have been described, including those of colitis, enterocolitis or perianal disease[3,4,9-12]. These gastrointestinal complications are associated with HPS 1 and HPS 4 subtypes, occur in 20%-30% of the cases[3,4], and have been the cause of death in 9% of the deceased HPS patients in Puerto Rico[6].…”
Section: Discussionmentioning
confidence: 99%
“…The granulomatous colitis associated with HPS shares features with both ulcerative colitis and CD. In fact, clinical presentation and friable erythematous mucosa with ulcerations from rectum to cecum are suggestive of ulcerative colitis[10-12], but they present pathologic findings consistent with CD and can be associated with perianal and perirectal disease resembling the typical anorectal findings often seen in patients with CD[4,9,12].…”
Section: Discussionmentioning
confidence: 99%
“…The colitis may respond to corticosteroids or anti‐TNF‐α drugs; surgical bowel resection is performed in refractory cases (Demirtas, Alahdab, Kani, Atug, & Imeryuz, 2019; Kouklakis et al, 2007; Mora & Wolfsohn, 2011). Abnormal endosomal membrane formation was suggested as an underlying cause for HPS colitis leading to ceroid lipofuscin formation, abnormal autophagy and phagocytosis, and inflammation (Felipez et al, 2010; Sofia et al, 2017). It was suggested that the presence of risk alleles in Crohn's disease‐associated genes, like NOD2 or ATG16L1 , in HPS subjects may contribute to developing colitis (Lozynska et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The underlying cause remains unknown. Abnormal endosomal (LRO‐related) membrane formation was suggested, leading to ceroid lipofuscin formation, abnormal autophagy and phagocytosis, inflammation (Felipez, Gokhale, & Guandalini, 2010; Sofia, Sakuraba, & Rubin, 2017). Some BLOC‐2 or BLOC‐3 deficient cases develop colitis (Huizing et al, 2000; Hussain et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Twenty percent patients of HPS associated with granulomatous colitis. The HPS types 1 and 4 are associated with a granulomatous enterocolitis affects in first or third decade [26,27]. Upper gastrointestinal involvement is rare with evidence of gastroduodenal ulcer with lymphocytic infiltration [28].…”
Section: Systemic Involvementmentioning
confidence: 99%